Assessing writing ability of the tenth grades of SMAN2 BL through guided question and answer - Lestari, I Dewa Ayu Made Mutiara (Journal of Language, Literature, Social and Cultural Studies, 2023)
In teaching learning process, assessment is very important in giving a score and feedback about the students' work in order to know the achievement of students’ ability. Arranging a good assessment will give a positive feedback for the teachers and also the students. In assessing students’ writing ability teachers must assess the students objectively to obtain accurate and appropriate information about students’ writing ability. The undertaking of the present study used ex posts facto research design. This quantitative descriptive study aimed to figure out the achievement of recount text writing ability of the tenth-grade students of SMAN2 BL which was assessed by using guided question and answer. The data required for the present study were gathered by means of administering guided question and answer to 50 samples. This study used random sampling technique with a lottery system to give equal opportunity for the entire population. The data of the research were analyzed and measured using a norm reference of five standard values. The findings reveal that there were 68.00% of the samples under study who were successful in writing recount text while 32.00% of the samples were unsuccessful in writing recount text which was assessed by using guided question and answer. The findings also clearly showed the achievement of the tenth-grade students of SMAN2 BL in academic year 2017/2018 in writing recount text which was assessed by using guided question and answer. It could stimulate the samples’ ideas in creating and organizing their ideas into a recount text.